COVID-19 in solid organ transplant recipients: initial report from national multicenter observational study «ROKKOR-recipient» - S. V. Gautier; A. O. Shevchenko; O. M. Tsirulnikova; S. M. Khomyakov; O. N. Kotenko; V. E. Vinogradov; I. N. Abyzov; G. D. Avetisyan; A. Yu. Anisimov; L. Yu. Artyukhina; M. T. Bekov; V. A. Berdinsky; et al. (Вестник трансплантологии и искусственных органов, 2020)
We herein present our initial report from «ROKKOR-recipient», a national multicenter observational study. The prevalence, risk factors, clinical manifestations and outcomes of the novel coronavirus disease 2019 (COVID-19) in solid organ transplant recipients receiving immunosuppressive therapy were investigated. The study enrolled 251 COVID-19 patients (220 kidney recipients, 7 liver recipients, 1 liver-kidney recipient, and 23 heart recipients). The subjects came from 20 regions in Russia. The symptoms, clinical presentation, imaging and lab test results, therapy and outcomes of COVID-19 were described. It was established that solid organ transplant recipients with COVID-19 have a higher risk of developing adverse events. Predictors of adverse events include associated cardiovascular diseases, pulmonary diseases, diabetes, and kidney failure. Symptoms of the disease include dyspnea, rash and catarrhal signs, as well as initial low blood oxygen saturation (SpO2 <92%), leukocytosis (white blood cell count >10 × 109/L), elevated creatinine levels (>130 μmol/L) and a marked decrease in glomerular filtration rate, requiring hemodialysis. Performing organ transplant surgery in COVID-19 does not increase the risk of adverse events but could save the lives of waitlisted terminally ill patients.